1983
DOI: 10.1080/00071668308416730
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of rye by chickens: Effect of microbial status, diet gamma irradiation and sodium taurocholate supplementation

Abstract: Several experiments were conducted to determine the influence of intestinal microflora when rye diets are fed to young chicks. In a conventional environment dietary rye severely depressed growth, amino acid and fat retention, and metatarsal bone ash. These conditions could be effectively alleviated by gamma irradiation of the diet and maintenance in a germ-free environment. In gnotobiotic chicks associated with streptococci dietary rye caused effects similar to those seen in a conventional environment, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…This was attributed to fat malabsorption induced by feeding rye, barley, or oats (Campbell et al 1983a (Classen et al 1985). This is reflected in a substantially reduced metabolizable energy that is correctable with enzyme supplementation (Rotter et al 1990a (Gohl and Gohl 1977), increased digesta viscosity.…”
Section: Pentosans As Growth-depressantsmentioning
confidence: 99%
“…This was attributed to fat malabsorption induced by feeding rye, barley, or oats (Campbell et al 1983a (Classen et al 1985). This is reflected in a substantially reduced metabolizable energy that is correctable with enzyme supplementation (Rotter et al 1990a (Gohl and Gohl 1977), increased digesta viscosity.…”
Section: Pentosans As Growth-depressantsmentioning
confidence: 99%
“…The addition of bile salts to poultry diets has resulted in an improvement of fat absorption in chicks (Kussaibati et al, 1982). Also, Campbell et al (1983) reported that adding of dietary sodium taurocholate improved lipid digestibility in broiler chickens. However, few studies have been conducted on the effects of bile salts on blood metabolites, especially liver enzymes activity, in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the greatest negative effect of intestinal contents viscosity done on the rate of digestion and the absorption of lipids among different nutrients [19,61,62]. This loss of digestibility and absorption is greater for saturated fat.…”
Section: Reducing the Viscosity Of The Git Contentsmentioning
confidence: 99%